Growth responses of two kenaf varieties (Hibiscus cannabinus L.) applied by different levels of potassium, boron and zinc - Salih, Rabar Fatah; Abdan, Khalina; Wayayok, Aimrun (Canadian Center of Science and Education, 2014)
The aim of this study was to determine the effect of potassium, boron and zinc rates on the growth of kenaf. Seeds of two kenaf varieties namely; FHH 925 and 4383 variety were planted on 26 September 2013. Plant growth was determined for both varieties. The growth characteristics which consist of plant height, stem diameter and leaf number were measured every two weeks for five times consecutively. The best result was achieved for both characteristics; stem diameter and leaf number for FHH 925 variety when potassium and boron added at rates of 150 and 1.5 kg/ha, respectively except plant height was better when potassium was at the same rate while boron and zinc were controlled. The results showed a significant impression on the kenaf growth. It would be apposite to choose better varieties of kenaf for the production purpose with using better controlling of macro and micronutrients.